2018
DOI: 10.1109/tps.2018.2833282
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Highly Dynamic, and Precise 30-kA Arbitrary Current Source

Abstract: High power current sources with high dynamic performance, ultra-low current ripple and absolute reference tracking accuracy are key elements for magnets (bumper, septum) that are used in accelerators. Similar requirements are also encountered in plasma research applications in fusion reactors as well as plasma research for future HVDC circuit breakers. There, the current source must be able to drive resistive/inductive and highly fluctuating loads without any compromise in its performance. In this paper, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…DC arc), a flexible, modular high current source based on a 3-phase interleaved buck converter has been successfully demonstrated at 3 kV and 3 kA [22], [23]. Based on this, a novel topology with series or parallel stack modules for higher requirements has been introduced in [24], further improved in [25]. Fig.…”
Section: Testing Methods For Breakersmentioning
confidence: 99%
“…DC arc), a flexible, modular high current source based on a 3-phase interleaved buck converter has been successfully demonstrated at 3 kV and 3 kA [22], [23]. Based on this, a novel topology with series or parallel stack modules for higher requirements has been introduced in [24], further improved in [25]. Fig.…”
Section: Testing Methods For Breakersmentioning
confidence: 99%
“…Due to the typically rather low switching frequency in MMC applications, the requirements concerning the synchronisation accuracy and the communication delay are less demanding. Nevertheless, for systems with higher switching frequencies (13) , the synchronisation accuracy must be much higher. For example, a switching frequency of 100 kHz with the same duty cycle precision (10 bit) would result in a required accuracy of 9.5 ns.…”
Section: Data Exchange Requirements In Modular Converter Systemsmentioning
confidence: 99%
“…High bandwidth and precise current sources with the ability to deliver step-like as well as arbitrary/controllable current waveforms are emerging nowadays, finding a broad spectrum of applications, such as power hardware-in-the-loop (P-HiL) simulations [1]- [3], driving accelerator magnets for medical and fusion energy applications [4]- [7] or testing equipment for HVDC grids [8], [9]. The specifications for these applications are ever increasing, as they often require a high current rating, with a high dynamic (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It should be observed that the two-level bucktype topology might not be the most efficient topology for the whole output voltage range that needs to be served (measured efficiency surpasses 98% for v c of 550V but is lower than 95% for v c lower than 50V at nominal current). However, efficiency and power density are rather secondary goals for the aforementioned applications, where high dynamic performance, low ripple and high modularity are considered primary goals [9]. Note also that due to the high effective switching frequency and the ripple cancellation that is ensured by the interleaved operation, a rather low output capacitance is used.…”
Section: Introductionmentioning
confidence: 99%